The Changing Landscape of Neuroscience Research, 2006–2015: A Bibliometric Study - Yeung, Andy Wai Kan; Goto, Tazuko K.; Leung, W. Keung (Frontiers in Neuroscience, 2017)
Background: It is beneficial to evaluate changes in neuroscience research field regarding research directions and topics over a defined period. Such information enables stakeholders to quickly identify the most influential research and incorporate latest evidence into research-informed education. To our knowledge, no study reported changes in neuroscience literature over the last decade. Therefore, the current study determined research terms with highest citation scores, compared publication shares of research areas and contributing countries in this field from 2006 to 2015 and identified the most productive journals. Methods: Data were extracted from Web of Science and Journal Citation Reports (JCR). Only articles and reviews published in journals classified under the JCR “Neurosciences” category over the period of interest were included. Title and abstract fields of each included publication were extracted and analyzed via VOSviewer to identify recurring terms with high relative citation scores. Two term maps were produced for publications over the study period to illustrate the extent of co-occurrence, and the impact of terms was evaluated based on their relative citation scores. To further describe the recent research priority or “hot spots,” 10 terms with the highest relative citation scores were identified annually. In addition, by applying Bradford's law, we identified 10 journals being the most productive journals per annum over the survey period and evaluated their bilbiometric performances. Results: From 2006 to 2015, there were 47 terms involved in the annual lists of top 10 terms with highest relative citation scores. The most frequently recurring terms were autism (8), meta-analysis (7), functional connectivity (6), default mode network (4) and neuroimaging (4). Neuroscience research related to psychology and behavioral sciences showed an increase in publication share over the survey period, and China has become one of the major contributors to neuroscience research. Ten journals were frequently identified (≥8 years) as core journals within the survey period. Discussion: The landscape of neuroscience research has changed recently, and this paper provides contemporary overview for researchers and health care workers interested in this field's research and developments. Brain imaging and brain connectivity terms had high relative citation scores.